The Quest for Stability: The Financial Stability View - Henk J. Brouwer; Dirk Schoenmaker; Jukka Vesala; Nicola Brink; Michael Kock (SUERF - The European Money and Finance Forum, 2010)
On September 3-4, 2009 SUERF and Utrecht University School of Economicsorganized the Colloquium "The Quest for Stability" in Utrecht, the Netherlands. The papers included in this SUERF Study are based on contributions to the Colloquium.
Keywords: E5; E52; E58; F36; G18; G28; 330; Financial regulation and supervision; financial stability; systemic risk; capital adequacy; Basel II; central banks; European financial framework; European System of financial supervisors; official support to financial institutions; Finanzkrise; Finanzmarktregulierung; Regulierung; Aufsichtsbehörde; Europa